Study of the contact angle of water droplet on the surface of natural K-feldspar with the combination of Ar+ polishing and atomic force microscopy scanning. (21st September 2021) - Rao, Shihang; Deng, Yajun; Cai, Wenjiu; Li, Zhenchao; Ye, Jianliang; Lu, Hailong
Graphical abstract: Highlights: The topographies of micro-sized water droplets on local homogeneous areas are obtained. More consistent contact angle data are yielded by the present method compared with traditional optical method. The influences of heterogeneity and roughness on the wettability of K-feldspar surface were reduced. Abstract: Wettability is a key property of a reservoir rock, which can significantly affect the distribution and transportation of fluids (gas, oil, water, etc.) in reservoir pores which are constructed with various minerals. As for sandstone reservoirs, quartz and feldspar are the common minerals of the framework. However, the study on the wettability of feldspar is much less than that of quartz probably due to the strong heterogeneity and complex composition of natural feldspar minerals. In this study, a method for measuring the contact angle of water droplet on a natural mineral surface is proposed by combining argon ion polishing technique with atomic force microscopy scanning (Ar + -AFM method). Compared with the traditional optical goniometer measurement, this method can apparently reduce the influence of heterogeneity on the wettability of K-feldspar surface and yield more consistent contact angle data.